Efektivitas Jumlah Ikan Nila (Oreochromis niloticus) Terhadap Pertumbuhan Tanaman Sawi Pakcoy (Brassica rapa L.) pada Sistem Akuaponik - Diah Karunia Binawati; Rikza Fardatus Sabila (UNIVERSITAS PGRI MADIUN, 2022)
Sawi pakcoy (Brassica rapa L) is one of the most well known kinds of vegetables in Indonesia. Farming innovation that can be utilized is hydroponics innovation. In hydroponics frameworks, creature discharges are given to plants to be separated into nitrates and nitrites through regular cycles and can be used by plants as supplements from fish squander. Tilapia (Oreochromis niloticus) is one of the freshwater fish products that are most popular by different gatherings. The motivation behind this review was to decide the impact of the quantity of tilapia (Oreochromis niloticus) on the development of mustard greens and the treatment of the ideal number of tilapia (Oreochromis niloticus) on the development of mustard greens (Brassica rapa L) utilizing hydroponics framework. Randomized square plan was utilized in this review with three medicines and nine replications. Information handling utilized one way ANOVA factual examination, if critical, further Duncan Numerous Reach Test (DMRT) was done. The aftereffects of the investigation of the quantity of leaves, wet weight and complete chlorophyll content of the Pakcoy Mustard (Brassica rapa L) plant with the ANOVA test showed critical numbers (P <0.005), accordingly the quantity of tilapia (Oreochromis niloticus) influenced the development of the Pakcoy Sawi (Brassica rapa L) plant. ). The aftereffects of the treatment of the quantity of tilapia (Oreochromis niloticus) 80 fish (P3) gave ideal outcomes on the development of the mustard greens (Brassica rapa L) with hydroponics framework.